The possibility of establishing forests and their environmental impact in Baghdad Governorate (Journal of the College of Basic Education, 2025)
The study addressed forests and their impact on human health, given their significant role in environmental development and growth. It aimed to understand the status of forests in Baghdad Governorate (the study area) and their positive impact on human health. The study results showed that the study area contains no forests, but rather neglected green spaces. Furthermore, the largest forest in the region, the (Nahrawan Forest), with an area of ​​5,580 dunams, has begun to be converted into a residential complex called the( Ali Al-Wardi Residential City).